A new non-indigenous Crassostrea species in Southwest Atlantic salt marshes affects mortality of the cordgrass Spartina alterniflora - Lomovasky, Betina Judith (2014)
Biological invasions in marine and coastal systems may produce new trophic and nontrophic interactions influencing the structure of the invaded community. In the intertidal salt marshes of Samborombón Bay (36°19′20″S, 56°46′26″W; mouth of La Plata River; Argentina), there is a new non-indigenous oyster species, Crassostrea sp., which settles on the dominant smooth cordgrass Spartina alterniflora. Here, we analyzed if the oyster affects S. alterniflora. Sampling showed that density of live plant was similar across intertidal levels, but there were higher density of dead plant stems at low intertidal levels. This pattern coincides with higher density and larger shell size of Crassostrea sp. at the low intertidal where oysters are attached to the basal part of the plant stems. An experiment manipulating oysters attached to S. alterniflora stems and oyster mimics shows that Crassostrea sp. can indeed increase mortality of S. alterniflora. The negative effect of bivalves on plant could be because several oysters settle around the Spartina stem, and by growing during the year, strangle the plants increasing their mortality rate. Together, all these evidences strongly suggest that these non-indigenous oysters can control the lower intertidal level of plant distribution in this system.